TEACHERS’ ROLES ON TALENT DEVELOPMENT OF HIGH SCHOOL STUDENTS IN LANGSA - Wahidah Wahidah (Jurnal Ilmiah Didaktika, 2021)
Teachers play important roles in developing students’ talents. This paper focuses on the roles of teachers in talents development from teachers and deputy head of students’ affairs perfective. They are deputy head of SMK 1, SMUN 4 and MAN 2 Langsa. The purpose is to clarify about teachers understanding of talents in secondary schools in Langsa and what’s the role of teachers in developing students’ talents. A qualitative research by interview conducted among teachers and the deputy head of students affairs show that there are several roles taken by teachers in developing students’ talents. They are (1) parent partners, (2) role models, (3) organizers, (4) motivators, (5) facilitators, and (6) supervisors. However, most teachers understand talents only come from five senses. As a result the currents focus of developing talents in high schools is about field talents while talents come from nature (characters) is not nurtured yet.